2023
DOI: 10.1002/smll.202303099
|View full text |Cite
|
Sign up to set email alerts
|

Ceo2/Cus Nanoplates Electroreduce Co2 to Ethanol with Stabilized Cu+ Species

Abstract: Copper‐based electrocatalysts effectively produce multicarbon (C2+) compounds during the electrochemical CO2 reduction (CO2RR). However, big challenges still remain because of the chemically unstable active sites. Here, cerium is used as a self‐sacrificing agent to stabilize the Cu+ of CuS, due to the facile Ce3+/Ce4+ redox. CeO2‐modified CuS nanoplates achieve high ethanol selectivity, with FE up to 54% and FEC2+ ≈ 75% in a flow cell. Moreover, in situ Raman spectroscopy and in situ Fourier‐transform infrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Notably, CeO 2 can stabilize in situ formed Cu δ + , and prevent the Cu δ + reduced to Cu 0 in CO 2 RR. [23][24] Accordingly, we propose a CeO 2 nanotube with morphology and chemical strategy to stabilize Zn δ + sites and enhance the durability of the electrocatalyst. The nanotube with confinement effect could stabilize the Zn δ + sites, and CeO 2 with the Ce 3 + /Ce 4 + redox could inhibit the electron accumulation around the unsaturated site and thus prevent the reduction degradation of active Zn δ + sites during CO 2 electrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, CeO 2 can stabilize in situ formed Cu δ + , and prevent the Cu δ + reduced to Cu 0 in CO 2 RR. [23][24] Accordingly, we propose a CeO 2 nanotube with morphology and chemical strategy to stabilize Zn δ + sites and enhance the durability of the electrocatalyst. The nanotube with confinement effect could stabilize the Zn δ + sites, and CeO 2 with the Ce 3 + /Ce 4 + redox could inhibit the electron accumulation around the unsaturated site and thus prevent the reduction degradation of active Zn δ + sites during CO 2 electrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Although Cu-NS at low potential (−1.0 V vs RHE) has high FE C 2+ (63.62%) and selectivity for C 2+ products, its hydrogen evolution reaction is serious, and the FE H 2 of Cu-NS (>12%) is mostly twice that of Cu 2 O-NS and CuO-NS (Figure f). Compared with some Cu-based catalysts reported so far, FE C 2+ of ultrathin Cu 2 O-NS reported in this work is better (Figure h). , In addition, based on linear sweep voltammetry (LSV) records (Figure S4a), Cu-NS is able to attain a higher current density (100 mA cm –2 ) at a lower potential, which reflects the serious hydrogen evolution reaction of Cu-NS once again. From the total current density information and the current density information on the single component (C 2 H 4 ), it can be seen that the current density of oxide catalysts was much lower than that of Cu-NS, and Cu 2 O-NS can achieve more C 2 H 4 conversion at lower current densities (Figure S4b,c).…”
Section: Resultsmentioning
confidence: 58%
“…[102] CeO 2 changes the oxidation state of Cu atoms to Cu + at the CuOÀ CeO 2 interface, resulting in the suppression of HER and the promotion of ethylene production. Recent research revealed that CeO 2 could be used as a self-sacrificing agent to stabilize the Cu + of CuS through the interface effect (Figures 10h, 10i), due to the facile Ce 3 + /Ce 4 + redox, as reported by Yang et al [103] CeO 2 -modified CuS nanoplates achieve high ethanol selectivity, with FE up to 54 %. The FE C2 + is 75 % in a flow cell with a total current density of 160 mA cm À 2 .…”
Section: Interface Engineeringmentioning
confidence: 66%
“…Reprinted with permission from Ref. [103] Copyright 2023, John Wiley and Sons. j) Reaction pathway on the interface of Cu/CeO 2 .…”
Section: Interface Engineeringmentioning
confidence: 99%